Lateral view fulcrum bending radiographs predict postoperative hypokyphosis after selective thoracic fusion in adolescent idiopathic scoliosis - Victoria Yuk Ting Hui; Jason Pui Yin Cheung; Prudence Wing Hang Cheung (Asian Spine Journal)
Study Design A retrospective observational study. Purpose To identify the surgical and preoperative risk factors on fulcrum bending radiographs for postoperative hypokyphosis in patients with Lenke 1 adolescent idiopathic scoliosis (AIS). Overview of Literature AIS is associated with thoracic hypokyphosis. Persistent hypokyphosis causes reduced pulmonary function and spinopelvic malalignment. Indications for Ponte osteotomies and releases to improve postoperative kyphosis restoration in patients with hypokyphosis are still unclear. Previous studies have demonstrated that kyphosis correction was limited by sagittal flexibility based on lateral view fulcrum bending radiographs. Methods Patients with Lenke 1 AIS undergoing posterior spinal fusion were included. Standing and fulcrum bending radiographs on the coronal and sagittal planes were analyzed at preoperative, immediate, and 2-year postoperative periods. The primary outcome was postoperative hypokyphosis (T5–12 thoracic kyphosis [TK] <20°). Risk factors for postoperative hypokyphosis were identified by multivariate logistic regression, and the optimal cutoff for significant risk factors was determined by receiver operating characteristic analysis. Results In total, 156 patients were included in the analysis, of which 68 (43.6%) were hypokyphotic at 2-year follow-up. Low T5–12 TK on lateral view fulcrum bending films (immediate postoperative odds ratio [OR], 0.870; 95% confidence interval [CI], 0.826–0.917; 2-year postoperative OR, 0.916; 95% CI, 0.876–0.959; p<0.001) and high convex side implant density (2-year postoperative OR, 1.749; 95% CI, 1.056–2.897; p=0.03) were significant risk factors for postoperative hypokyphosis. Other baseline demographic and surgical factors did not affect postoperative kyphosis correction. The T5–12 TK cutoff on fulcrum bending for 2-year postoperative hypokyphosis was 12.45° (area under the curve, 0.773; 95% CI, 0.661–0.820). Conclusions Fulcrum bending radiography is useful in assessing coronal and sagittal flexibility for preoperative planning. In patients with T5–12 kyphosis <12.5° on lateral view fulcrum bending radiographs, Ponte osteotomies or releases, or a decrease in convex side implant density should be considered to improve kyphosis restoration and reduce the risk of 2-year postoperative hypokyphosis.